What does "quality" look like for post-2015 education provision in low-income countries? An exploration of stakeholders' perspectives of school benefits in village LEAP schools, rural Sindh, Pakistan. (January 2016) - Jerrard, Jane
Highlights: Social capital should be included in the discourse of "quality" education. Contextualized, iterative educational provision facilitates social change. Teachers' transformational process shapes perceptions of school benefits Abstract: The provision of quality education for the poor and marginalized is intertwined with addressing social justice concerns. Parents need convincing that the cost of sending their children to school is offset by tangible benefits. This article draws on a study of perceptions of school benefits and the factors and processes shaping them, in rural Sindh, Pakistan. It responds to the strategies advocated in the Global Monitoring Report 2013–2014 for solving the "quality" crisis and to the widespread struggle in low-income countries to recruit sufficient, trained teachers to achieve EFA and provide education that becomes a catalyst for social change.